(untitled) (Medico Legal Update, 2019)
The purpose of this study was to investigate the effects of repetition time changes during barbell curl exercise on EMG responses.In this study, the subjects were selected from twelve men in their twenties who had more than 3 years of resistance exercise experience. In this case, the subjects were randomly assigned to three conditions at intervals of one week with different rest interval and intensity (50%1RM/1min, 70%1RM/2min, 90%1RM/3min). When each condition was performed, each one repetition time and iEMG of the agonist were measured and reviewed. In each instance, a statistical analysis was performed by repeated measures of two-way ANOVA, with a p value=.05. In the review of the results of this study, iEMG of flexor carpi ulnaris during the performance of the barbell curl movement increased significantly with the occurrence of performance speed decrease point in all intensity,. and was significantly noted with the progression of the set only at 50%1RM and 70%1RM. The point of occurrence of repetition speed decrease point was significantly different according to exercise intensity. Generally speaking, the heavier the weight, the closer was the point of performance speed decrease point and the end of exercise. To that end, the point of occurrence of performance speed decrease point according to the set also showed a significant difference. In this case, as the set progressed, there was a tendency that the point of performance speed decrease point was close to the point of stopping motion. There In conclusion, it is important to consider the fatigue facstor associated with decreased performance during resistance exercise, and the important role of a supporter should be considered and utilized when exercise speed is decreased as an exercise set progresses during a regimen.